Overcoming barriers to off-patent drug repurposing: a lifecycle-based policy solutions - Garcia-Diaz, Mario; Epstein, David; Espin, Jaime (Frontiers in Pharmacology, 2025)
IntroductionDrug repurposing leverages existing medicines to reduce time and costs for exploring new therapeutic indications. However, off-patent medicines do not provide enough private incentives for investment, and prescribing by active ingredient can be a major barrier. Academics and non-profit sponsors also face regulatory barriers.MethodsThis study combined a structured literature review with a questionnaire completed by 25 drug repurposing experts to identify key challenges and policy solutions across the full lifecycle of off-patent drug repurposing.ResultsPublic funding is generally available for the early-stage research, where opportunities often arise from off-label uses and real-world evidence. However, limited support for confirmatory clinical trials, combined with the predominance of academics and non-profit sponsors lacking regulatory objectives, reduces the likelihood of successful authorisation to below 30%. Policy solutions include prioritising research into rare diseases and other conditions with unmet health needs, and call for a more prominent role of governments in public investment and in reinforcement of public–private partnerships. Substitution in community pharmacies remains a major challenge, which may be addressed through indication-based differentiation and enhanced dispensing controls. Some innovative public intervention mechanisms, such as Social Impact Bonds and the InterVentional PharmacoEconomics proposal, offer potential, although real-world experience is still limited.ConclusionOff-patent drug repurposing faces persistent financial and regulatory barriers that require a central role from academics and non-profit sponsors, supported by governmental engagement throughout the lifecycle. Although steps have been taken in recent years, efforts remain insufficient, and structural and political barriers continue to hinder broader implementation.